Ultra-simple wearable local sweat volume monitoring patch based on swellable hydrogels. Issue 1 (4th December 2019) - Zhao, F. J.; Bonmarin, M.; Chen, Z. C.; Larson, M.; Fay, D.; Runnoe, D.; Heikenfeld, J.
Abstract : Presented is an ultra-simple wearable local sweat volume monitoring patch based on swellable hydrogels. Abstract : Quantifiably monitoring sweat rate and volume is important to assess the stress level of individuals and/or prevent dehydration, but despite intense research, a convenient, continuous, and low-cost method to monitor sweat rate and total sweat volume loss remains an un-met need. We present here an ultra-simple wearable sensor capable of measuring sweat rate and volume accurately. The device continuously monitors sweat rate by wicking the produced sweat into hydrogels that measurably swell in their physical geometry. The device has been designed as a simple to fabricate, low-cost, disposable patch. This patch exhibits stable and predictable operation over the maximum variable chemistry expected for sweat (pH 4–9 and salinity 0–100 mM NaCl). Preliminary in vivo testing of the patch has been achieved during aerobic exercise, and the sweat rates measured via the patch accurately follow actual sweat rates.